Agro-climatic services help 500,000 farmers in Latin America better plan their crops - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS scientists developed, tailored and implemented actions to support the implementation of climate services for agriculture in Colombia, Nicaragua, Honduras and Guatemala. These include the creation of 22 Local Technical Agroclimatic Committees (LTACs), the automation of the Climate Predictability Tool, and the development of capacities in Ministries of Agriculture, farmers organizations, and meteorological services.